TECHNOLOGY ADDICTION AMONG STUDENTS - Khaleel , Mousa; AlHawamdeh, Mekhled (International Journal of Psychosocial Rehabilitation, 2020)
This research paper is primarily concerned with the technological addiction among human being and its impact on the health of individual. Technological advancement is not only having significant impact on the mental health of the students but also has significant impact on the physical health of the students. Students day-by-day become less attentive towards their study and get addicted to technological devices (Muduli, 2014). Among total population of the world, youth is most vulnerable groups; youth or students are in charge of taking responsibility of country’s future. If they do not work, then it is utterly impossible for them to get new dimension. The study is designed in such a way to understand what types of tech devices are used by youth. Time spent with the gadgets has noteworthy impact on the mental health and lifestyle of students. Reason behind technological addiction and impact of this on the society has been understood clearly with the help of this study.Nevertheless, in the era of technological development, human beings are completely driven by technological implements. It has covered the entire human community; people have depended on the technological implements & internet is increasing continuously. People do not like loose the compliment like tech savvy and in order to retain their image in group, teenagers are completely engrossed with the technological advancement. For better analysis of the paper, research has chosen Primary Quantitative Data Analysis Process. Simple Random Sampling has been chosen for analysis; 100 respondents have been chosen among them 40 parents and 60 students of different age groups. With the help of graphs and charts data has been analyzed.